The use of water quality Index (Canadian model) to determine the validity of the Euphrates River (mid Euphrates / Iraq) for Irrigation* - Y. K. Al-Rekabi, Hussain; B. G. Al-Ghanimy, Dunia (Al-Qadisiyah Journal of Pure Science, 2018)
The current study conducted to assess the Euphrates river (Mid Euphrates-Iraq) for irrigation purposes by adoption of water quality index - Canadian model- as an efficient means to identify the water validity for different purposes, four sites have been selected and samples were collected from these locations for the period between May 2013 to April 2014 and conducted Some physical and chemical tests, that included (electrical conductivity, pH, sodium adsorption ratio, chloride, boron, lead, copper, zinc, cadmium, manganese, chromium). Results confirmed that the values ​​of water quality guide for irrigation ranged from (75.7 - 37.18), that means the waters of the Euphrates River in the study area located between the two categories (fair - poor).